2019
DOI: 10.1136/bcr-2019-231114
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal lymphoma presenting as primary hypoadrenalism in the elderly

Abstract: Adrenal lymphoma causing primary hypoadrenalism in the elderly is a very rare finding. We describe a case of an 85-year-old man who was admitted to our hospital. He had a short history of hypotension and unresponsiveness. He was referred to the endocrine team, after a CT scan of his thorax abdomen and pelvis demonstrated significant enlargement of both his adrenal glands with associated lymphadenopathy. This scan was originally done to rule out an occult intra-abdominal malignancy. In addition, a tetracosactid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Majidi et al finally concluded that there is significant heterogeneity in the manifestation of primary adrenal lymphoma. 7 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Majidi et al finally concluded that there is significant heterogeneity in the manifestation of primary adrenal lymphoma. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Majidi et al finally concluded that there is significant heterogeneity in the manifestation of primary adrenal lymphoma. 7 Primary adrenal lymphoma has been characterised as either unilateral or bilateral lymphoma in a patient without a medical history of lymphoma elsewhere and with the adrenals being the predominantly involved organ. 7 About 70% of cases of primary adrenal lymphoma are bilateral.…”
Section: Case Report Discussionmentioning
confidence: 99%
See 3 more Smart Citations